COMPARATIVE STUDY OF BONE MINERAL DENSITY IN HIGH AND LOW INCOME SCHOOL CHILDERN - Syed Mujahid; Samia Samar; M. Shakeel Baig; Aaliya Syed (Journal of the Dow University of Health Sciences, 2009)
To compare the bone mineral density [B M D] and associated dietary and physical activity factors in low and high socio economic status (SEC) groups of childern.